Bioenergetic Heterogeneity in Mycobacterium tuberculosis Residing in Different Subcellular Niches - Ajit Kumar Akela (American Society for Microbiology, 2021)
ATP/ADP levels guide bacterial cells, whether to replicate or to enter nonreplicating persistence. However, tools for measuring ATP/ADP levels with spatiotemporal resolution are lacking.